Do Dollar Forecasters Believe too Much in PPP? - Lukas Menkhoff; Rafael R. Rebitzky; Michael Schröder (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2005)
This paper extends earlier studies on exchange rate expectations' formation by using new data and adding information about forecasters' reliance on fundamental analysis for the first time. We replicate the conventional result of non rational expectations. Moreover, biases in expectations are identified as professionals significantly belief too much in mean reversion, mean being represented by PPP. When respondents are grouped on their reliance to fundamental analysis, fundamentalists reveal an even stronger bias. Those, who rely the least on fundamentals – preferring technical analysis instead ?, show a significantly smaller bias towards PPP in lieu of expecting too much trend extrapolation. Biased beliefs will grow stronger when the US Dollar is further away from PPP. Finally, the accuracy of the expectations is poor for both groups however we find directional forecasting ability.
Keywords: G14; F31; 330; Exchange rate expectations; forecasting; fundamental analysis; technical analysis; purchasing power parity